Monetary and fiscal policy related issues: regional input Poland - Katarzyna Zukrowska; Dominik Sobczak (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
Such an exceptional event as the creation of the EMU and the euro has not had happened never before. The most common challenges concerning EMU and the euro are: fiscal policy making, monetary policy making, euro area being a non-optimal currency area and the political legitimacy of EMU. It is worthwhile stressing that economic policies except from monetary policy are still framed by the individual member states or by coordination with others. It is than of the utmost importance to define what are the chances for the euro to preserve its influence and to combat inflation after accession of ten new member states. This regional input provides empirical insights on these issues for Poland and the Czech Republic.
Keywords: E42; E52; 330; Monetary Policy Modelling; EMU; Regional Input; Monetary and Fiscal Policies